Punch line - McMann, Donald J. (My University, 2020)
It’s about a man’s serious attempt to make a living writing jokes. “A man walks into a bar. He’s carrying a rabbit in a cage. “What’s with the caged rabbit?” asks the bartender. “Isn’t it obvious? I’m afraid of losing my hare.”
Keywords: fiction; wit and humor; humorists